A revision of the ant genus Probolomyrmex (Hymenoptera: Formicidae: Proceratiinae) in Australia and Melanesia - Shattuck, S.; Gunawardene, Nihara; Heterick, Brian E. (Magnolia Press, 2012)
Five species of the rarely encountered ant genus Probolomyrmex are known from Australia and Papua New Guinea, four of which are described here for the first time. Two species belong to the greavesi species-group (P. greavesi, P. latalongus sp. n.)while three belong to the longinodus species-group (P. aliundus sp. n., P. newguinensis sp. n., P. simplex sp. n.). The genus is now known to occur broadly across northern Australia and P. newguinensis and P. simplex are the first species of the genus described from Papua New Guinea. A key to Australian and Melanesian species is provided.